1994
DOI: 10.3109/10715769409056568
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Scavenging Activity of Spin-Labeled Nitrosourea and Triazene Derivatives

Abstract: Superoxide scavenging activities (SSA) of newly synthesized spin-labeled nitrosourea and triazene derivatives, and their precursor nitroxides were investigated by the ESR/spin-trapping method using the spin trap 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) and hypoxanthine/xanthine oxidase as the superoxide-generating system. The spin-labeled nitrosoureas, triazenes and their precursor nitroxides exhibited excellent SSA, whereas clinically used nitrosourea and triazene, which do not contain the nitroxide moiety, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Additionally, tetrahydrobiopterin, a cofactor of NOS, was found to rapidly oxidize ⅐ NO through the generation of O 2 . (44), respectively). The rank order of efficacy for the four compounds tested was the same in the cell culture and SIN-1 experiments: SOD Ͼ TEMPOL Ͼ CP Ͼ ECP (Table I).…”
Section: ⅐ No Release By Endothelial Cells In the Presence Of Nitrox-mentioning
confidence: 91%
“…Additionally, tetrahydrobiopterin, a cofactor of NOS, was found to rapidly oxidize ⅐ NO through the generation of O 2 . (44), respectively). The rank order of efficacy for the four compounds tested was the same in the cell culture and SIN-1 experiments: SOD Ͼ TEMPOL Ͼ CP Ͼ ECP (Table I).…”
Section: ⅐ No Release By Endothelial Cells In the Presence Of Nitrox-mentioning
confidence: 91%
“…4(b)) bringing to controls showed that in a great extent synthetic antioxidants were able to neutralize ongoing oxidative processes. This finding may be explained by their well expressed scavenging activity against superoxide radicals 40,10 . The lowest ROS levels were observed after P. corylifolia treatment in liver and blood of mice.…”
Section: Discussionmentioning
confidence: 96%
“…Our study confirms once again in vivo protective abilities of SLENU against oxidative toxicity of clinically used antitumor antibiotics and radiation 38,39 . Gadjeva and co-workers, 1994 40 using in vitro spintrapping EPR method demonstrated that SLENU possessed high superoxide radical scavenging activity (SSA) even higher than antioxidant Trolox. Later on well expressed in vitro SSA for SLCNUgly was also found 10 .…”
Section: Discussionmentioning
confidence: 99%
“…EPR spectroscopy is a highly sensitive technique utilized for investigation of free radical scavenging capacity and radical structures in synthetic and naturally isolated antioxidants (9,10,11,12,13). Formerly, by in vitro EPR spin trapping technique we reported a well expressed superoxide anion scavenging activity for SLENU due to the presence of the nitroxyl radical moiety in its structure (4).As is seen on (Fig. 3A) in the solution of SLENU the typical triplet EPR signal of the nitroxyl free radical was registered, while in the aqueous solution of SQGD an EPR signal with a single line was recorded (Fig.…”
Section: Amentioning
confidence: 99%
“…In recent years, increasing studies are performed on the effects of the treatment of many diseases with combinations of synthetic medicines and other radical scavengers. Use of appropriate natural and synthetic antioxidant substances reduces the level of lipid peroxidation and increases the activity of antioxidant enzyme defense system and ultimately reduces radiotherapy-and chemotherapy-induced oxidative stress and negative consequences (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15). The purpose of this study was to evaluate and compare the free radical scavenging activity and protective properties of the natural product SQGD isolated from a radioresistant bacterium Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%